Numerical solution and mathematical modelling of mass transport from medicated stent - Ali, Akhtar; Hussain, Majid; İnç, Mustafa; Hussan, Muhammad; Ul Rahman, Jamshaid (Iop Publishing Ltd, 2022)
Restenosis in arteries is amajor problemwhich can be controlled by using medicated stents. The controlled drug transport from medicated stents has a great effect in decreasing restenosis in arteries. Drug is coated on stents to keep away fromthe re-narrowing of the arterywall. This device has an advantage of a flexible time delivery of a curative drug to the adjoining blood vessel tissues. The aim of this study is to formulate amathematicalmodel which describe the process of drug transport fromarterialwall and medicated stent. For this purpose, a 3Dmodel is investigated to measure the impact of mass transport fromdrug eluting stent. The blood flow is modelled by dimensionlessNavier stokes equations and the concentration of drug is driven by dimensionless' convection diffusion equation. The effect of diffusive and advective forces are discovered and these forces can be used to control the drugmass transport. Moreover, the effect of dimensionless parameters such as Peclet number Pe, porosity k and Re onmass transport frommedicated stent and tissue layers is investigated. Characteristic Based SplitGalerkin (CBSG) technique is applied to solve the dimensionless equations. In the application of stent- based drug delivery, the governing equations in this explorationgive the premise of a plan for examining and computingmass transport inmedicated stent and artery wall. The numerical results support to offer a good insight into the possible impacts of various parameters.
Keywords: drug eluting stent; characteristic based split Galerkin method; numerical simulation